2017
DOI: 10.1016/j.bmc.2016.11.059
|View full text |Cite
|
Sign up to set email alerts
|

α-Pyrone derivatives, tetra/hexahydroxanthones, and cyclodepsipeptides from two freshwater fungi

Abstract: Eighteen (1-18) and seven (1, 4, 6-8, 17 and 18) compounds were isolated from organic extracts of axenic cultures of two freshwater fungi Clohesyomyces sp. and Clohesyomyces aquaticus (Dothideomycetes, Ascomycota), respectively. Compounds 1-12 belong to the α-pyrone class of natural products, compounds 13 and 14 were tetrahydroxanthones, compounds 15 and 16 were hexahydroxanthones, while compounds 17 and 18 were cyclodepsipeptides. The structures were elucidated using a set of spectroscopic and spectrometric t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
(93 reference statements)
0
21
0
Order By: Relevance
“…They were selective and competitive receptor antagonists of the human NK 2 receptor [ 219 ]. Both Sch 217048 ( 346 ) and Sch 378161 ( 348 ) were also isolated from the freshwater fungus Clohesyomyces aquaticus [ 220 ].…”
Section: Cyclic Decadepsipeptidesmentioning
confidence: 99%
“…They were selective and competitive receptor antagonists of the human NK 2 receptor [ 219 ]. Both Sch 217048 ( 346 ) and Sch 378161 ( 348 ) were also isolated from the freshwater fungus Clohesyomyces aquaticus [ 220 ].…”
Section: Cyclic Decadepsipeptidesmentioning
confidence: 99%
“…Moreover, the relative configuration of 6 was established to be 6R*, 7S*, 8R* and 11R* by X-ray crystallography using Mo Ka radiation (Figure 4). C-11, C-6 and C-10, OH-1 to C-2, C-13 and C-1 indicated that OH-1 and OH-11 were attached to C-1 and C-11, respectively [22,23]. Selected key correlations in the observed NMR spectrum are shown in Figure 3.…”
Section: Resultsmentioning
confidence: 96%
“…HMBC correlations from the O-methyl proton signal H 3 -15 to the carboxylic carbon C-14 confirmed that the O-methyl group was located at C-14. HMBC correlations from OH-11 to C-11, C-6 and C-10, OH-1 to C-2, C-13 and C-1 indicated that OH-1 and OH-11 were attached to C-1 and C-11, respectively [ 22 , 23 ]. Selected key correlations in the observed NMR spectrum are shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Natural products from a variety of sources have been reported to have Pth1 inhibitory activity [16,26,27]. We identified a readily abundant, local natural product which demonstrated Pth1 inhibition, the ethanol extract from Salvinia minima .…”
Section: Resultsmentioning
confidence: 99%